Hemothorax due to a ruptured esophageal gastrointestinal stromal tumor: case report - Shohei Ohki; Naoki Enomoto; Daiki Kato; Shusuke Yagi; Hitomi Wake; Kyoko Nohara; Hideki Miyazaki; Toru Igari; Norihiro Kokudo; Kazuhiko Yamada (Surgical Case Reports)
Abstract Background Esophageal gastrointestinal stromal tumors (GISTs) are rare tumors of the gastrointestinal interstitium, and comprise less than 0.7% of all GISTs. The presentation of esophageal GIST is relatively benign, commonly characterized by symptoms of dysphagia and gastrointestinal bleed. On the contrary, it is highly unusual for these tumors to present as surgical emergencies. Case presentation Here, we describe a case of hemothorax secondary to the rupture of a massive (19 cm) esophageal GIST in a 79-year-old male. The patient presented with mild back pain, vomiting, and hypotension. A CT scan revealed significant mediastinal enlargement and left hemothorax. We conducted an emergency thoracotomy which revealed a 19 × 15 × 7 cm ruptured esophageal tumor that was bleeding profusely into the left thoracic cavity. Piecemeal resection without esophagectomy was performed to achieve hemostasis. Pathological evaluation of resected tissue confirmed the diagnosis of GIST. The patient was provided adjuvant imatinib therapy and remains progression-free at the 10-month follow-up. Conclusions To the best of our knowledge, this is the first reported case of life-threatening hemothorax caused by a ruptured esophageal GIST. Findings from this case may aid in the diagnosis and management of these rare tumors.